To find 6x7 using 3x7, you can simply double the result of 3x7. This is because multiplication is distributive over addition, meaning that multiplying a number by a sum is the same as multiplying the number by each addend and then adding the products. In this case, 6x7 can be thought of as (3+3)x7, which equals 3x7 + 3x7, or 21 + 21, which equals 42.
aadawd
6x - 7 = 35 Therefore, 6x = 42 x = 42/6 x = 7
No it equals 35
No. 35 divided by 8 equals 4.375 .35 divided by 5 equals 7 .
6x7=42
a = 16
x=5
To find 6x7 using 3x7, you can simply double the result of 3x7. This is because multiplication is distributive over addition, meaning that multiplying a number by a sum is the same as multiplying the number by each addend and then adding the products. In this case, 6x7 can be thought of as (3+3)x7, which equals 3x7 + 3x7, or 21 + 21, which equals 42.
n=30, a value under 35.
aadawd
6 x 7 is equal to 2 x 3 x 7. If you find the solution to 3 x 7, you can multiply it by 2 to get 6 x 7.
6x7=42
6x7 equle = 42
6x - 7 = 35 Therefore, 6x = 42 x = 42/6 x = 7
6x7=42 42=5=47 so 6x7+5=47
If x equals 35, then -x equals -35.